YTHDF3 facilitates translation and decay of N(6)-methyladenosine-modified RNA - Shi, Hailing (Cell Res, 2017)
N(6)-methyladenosine (m(6)A) is the most abundant internal modification in eukaryotic messenger RNAs (mRNAs), and plays important roles in cell differentiation and tissue development. It regulates multiple steps throughout the RNA life cycle including RNA processing, translation, and decay, via the recognition by selective binding proteins. In the cytoplasm, m(6)A binding protein YTHDF1 facilitates translation of m(6)A-modified mRNAs, and YTHDF2 accelerates the decay of m(6)A-modified transcripts. The biological function of YTHDF3, another cytoplasmic m(6)A binder of the YTH (YT521-B homology) domain family, remains unknown. Here, we report that YTHDF3 promotes protein synthesis in synergy with YTHDF1, and affects methylated mRNA decay mediated through YTHDF2. Cells deficient in all three YTHDF proteins experience the most dramatic accumulation of m(6)A-modified transcripts. These results indicate that together with YTHDF1 and YTHDF2, YTHDF3 plays critical roles to accelerate metabolism of m(6)A-modified mRNAs in the cytoplasm. All three YTHDF proteins may act in an integrated and cooperative manner to impact fundamental biological processes related to m(6)A RNA methylation.